Prognostic implications of left atrial dilation in aortic regurgitation due to bicuspid aortic valve. Issue 2 (8th April 2021) - Butcher, Steele C; Fortuni, Federico; Kong, William; Vollema, E Mara; Prevedello, Francesca; Perry, Rebecca; Ng, Arnold Chin Tse; Poh, Kian Keong; Almeida, Ana G; González-Gómez, Ariana; Shen, Mylène; Yeo, Tiong-Cheng; et al.
Abstract : Objective: To investigate the prognostic value of left atrial volume index (LAVI) in patients with moderate to severe aortic regurgitation (AR) and bicuspid aortic valve (BAV). Methods: 554 individuals (45 (IQR 33–57) years, 80% male) with BAV and moderate or severe AR were selected from an international, multicentre registry. The association between LAVI and the combined endpoint of all-cause mortality or aortic valve surgery was investigated with Cox proportional hazard regression analyses. Results: Dilated LAVI was observed in 181 (32.7%) patients. The mean indexed aortic annulus, sinus of Valsalva, sinotubular junction and ascending aorta diameters were 13.0±2.0 mm/m 2, 19.4±3.7 mm/m 2, 16.5±3.8 mm/m 2 and 20.4±4.5 mm/m 2, respectively. After a median follow-up of 23 (4–82) months, 272 patients underwent aortic valve surgery (89%) or died (11%). When compared with patients with normal LAVI (<35 mL/m 2 ), those with a dilated LAVI (≥35 mL/m 2 ) had significantly higher rates of aortic valve surgery or mortality (43% and 60% vs 23% and 36%, at 1 and 5 years of follow-up, respectively, p<0.001). Dilated LAVI was independently associated with reduced event-free survival (HR=1.450, 95% CI 1.085 to 1.938, p=0.012) after adjustment for LV ejection fraction, aortic root diameter, LV end-diastolic diameter and LV end-systolic diameter. Conclusions: In this large, multicentre registry of patients with BAV and moderate to severe AR, left atrial dilation was independently associated with reduced event-free survival. The role of this parameter for the risk stratification of individuals with significant AR merits further investigation.